Synchronizability of Multi-Layer Dual-Center Coupled Star Networks - Zhu, Jian; Huang, Da; Yu, Zhiyong; Pei, Ping (Frontiers in Physics, 2021)
This paper calculates the Laplacian spectrums of multi-layer dual-center coupled star networks and multi-layer dual-center coupled star-ring networks from the main stability equation (MSF), and obtains important indicators reflecting the synchronizability of the above two network structures, and discusses the relationship among the parameters, i.e., the number of layers, nodes, inter-layer and intra-layer coupling strength in the case of unbounded and bounded synchronous region. Some numerical simulations are given to illustrate the effectiveness of the theoretical results. Finally, it is found that the synchronizabilities of the two sorts of networks studied in this article are the same, in addition, the two single-center network structures with the two structures under the same conditions and find that the synchronizability of the cases in which the two hub nodes is weaker than that of the single-center network.